Carriage of meticillin‐resistant staphylococci between humans and animals on a small farm. Issue 3 (June 2016) - Loncaric, Igor; Künzel, Frank; Klang, Andrea; Wagner, Regina; Licka, Theresia; Grunert, Tom; Feßler, Andrea T.; Geier‐Dömling, Dorothe; Rosengarten, Renate; Müller, Elke; Reissig, Annett; Spergser, Joachim; et al.
Abstract : Background: Meticillin‐resistant staphylococci (MRS) are pathogens of increasing importance to human and animal health worldwide. Transmission of meticillin‐resistant Staphylococcus aureus (MRSA) between animals and humans has been well documented. By contrast, information about transmission of other Staphylococcus spp. is limited. Hypothesis/Objectives: The aim of this study was to screen animals and humans on a small farm for nasal carriage of MRS and to assess interspecies exchange. Methods: After detection of MRSA in a lung sample of a deceased cat, which lived on a small mixed farm, nasal swabs were taken within two weeks, four and 16 months from other animals of various species and humans living on the farm. Swabs were cultured for MRS which were then characterized molecularly. Results: MRSA and meticillin‐resistant coagulase negative staphylococci (MRCoNS), including Staphylococcus haemolyticus, S. epidermidis and S. fleurettii, were isolated from humans and different animal species. Typing of the MRS revealed isolates with the same characteristics in different human and animal hosts. Conclusions and clinical importance: To the best of the authors' knowledge, this is the first report of carriage of both MRSA and MRCoNS among humans and various animals within a shared environment. The detection of strains with indistinguishable molecular characteristics strongly suggested transmission of these MRS between the various animal species and humans. Abstract : Background. – Meticillin‐resistant staphylococci (MRS) are pathogens of increasing importance to human and animal health worldwide. Transmission of meticillin‐resistant Staphylococcus aureus (MRSA) between animals and humans has been well documented. By contrast, information about transmission of other Staphylococcus spp. is limited.Hypothesis/Objectives – The aim of this study was to screen animals and humans on a small farm for nasal carriage of MRS and to assess interspecies exchange.Conclusions and clinical importance – To the best of the authors' knowledge, this is the first report of carriage of both MRSA and MRCoNS among humans and various animals within a shared environment. The detection of strains with indistinguishable molecular characteristics strongly suggested transmission of these MRS between the various animal species and humans.